(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Knowledge of cardiovascular diseases and improved diagnostic capacity is rapidly expanding with the advancement of medical sciences. However, heart diseases are a challenge to human life. Few important therapeutic targets for cardiovascular diseases were collected from mining of various bibliographic sources. Different proteins and bioactive small molecules are taken into consideration for target search. From ancient times, medicinal plants are shown to have remedial effect on cardiovascular system of human body, yet their modes of action are not completely understood till now. Selected plant derivatives, which have been examined under in vitro conditions to be effective against various heart diseases, were subjected to molecular docking with proposed targets using a bioinformatics tool, Hex 8.0. We have explored eight targets for five types of cardiovascular diseases and ten different ligands from herbal plants with a brief description about the cardiovascular diseases, their symptoms, target, ligand, source of the ligand and their mechanism of action. All the reported synthetic and phytocompounds were found to have good binding energies with all potential disease targets. Among all, Forskolin is found to be the best inhibitor of Angiotensin II type I receptor with the E-score of -369.96 for Atherosclerosis.